2017
DOI: 10.1111/sjop.12401
|View full text |Cite
|
Sign up to set email alerts
|

Do adapted vignettes improve medical decision‐making capacity for individuals with Alzheimer's disease?

Abstract: Medical decision-making capacity (MDC) is known to decline in individuals with Alzheimer's disease (AD). The vignette method uses hypothetical information as a prerequisite for measuring the capacity to make well-informed decisions to clinical trials. Our aim was to investigate if adapted vignettes can help individuals with mild AD to assimilate information, make decisions and express them in an understandable way, compared to corresponding decisions based on linguistically more demanding vignettes, as measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Since some studies did not show the effectiveness of decision-making support for people with AD ( Thalen et al, 2017 ; Palmer et al, 2018 ), decision-making support might rather cause their confusion. However, thinking about people with AD and explaining politely when they make decisions are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since some studies did not show the effectiveness of decision-making support for people with AD ( Thalen et al, 2017 ; Palmer et al, 2018 ), decision-making support might rather cause their confusion. However, thinking about people with AD and explaining politely when they make decisions are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In financial decision-making, semantic memory is linked to financial knowledge, while episode memory and visuospatial ability are related to numeracy ( Gamble et al, 2015 ). Working memory ( Stormoen et al, 2014 ; Thalen et al, 2017 ), short-term verbal memory ( Earnst et al, 2000 ; Thalen et al, 2017 ), verbal knowledge ( Stormoen et al, 2014 ), and semantic knowledge ( Earnst et al, 2000 ) might be involved in medical decision-making capacity. Thus, poor memory may affect decision-making in patients with AD.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Stacey et al (2014) said that the behaviour demonstrated by health professionals in simulated situations will closely resemble their behaviour in the equivalent clinical situations. Thalén et al (2017) said that although vignettes of clinical situations have been criticised, decision-making regarding a hypothetical situation reflects decision-making in real life. The debate around whether simulation reflects actual behaviours should be recognised and acknowledged as a potential limitation.…”
Section: The Main Strengths and Limitations Of Vignettesmentioning
confidence: 99%
“…Instruments to assess capacity have been tested in neurological populations including brain tumors, 1,4,5,10-13 dementia, 3, Parkinson disease, 18,47,48 neuropsychiatric disorders, 3,23,46 stroke, 49 and MS. 50,51 These instruments usually seek to test 4 abilities underpinning capacity: understanding, appreciation, reasoning, and choice. This can be achieved by tailoring the instrument to real-life (clinical) decisions facing the patient, 3,12,17,33,36,40 but has more often been studied using hypothetical clinical vignettes, 1,4,5,10,11,13,18,[20][21][22][23]25,[27][28][29][30][31][32]34,35,[37][38][39]41,42,45,47,48,[50][51][52][53]…”
Section: Tools To Measure Medical Capacitymentioning
confidence: 99%